The Role of Emotional Intelligence in the Relationship between Perceived Stress and Student’s Mental Health: A Conceptual Framework - Muhamad, Mira Qerul Barriah; Ahmad, Nur Azreen Farihah; Abdullah Thani, Ayu Kamareena; Rosely, Nurhidayah; Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim (International Journal of Accounting, Finance and Business, 2025)
: Past researchers identified a strong relationship between perceived stress and students’ mental health. Although various studies have been conducted on the stress related factors, a thorough review of the literature highlights some research gaps. Firstly, there are few studies that discuss the role of emotional intelligence as the personal resource to buffer the relationship between perceived stress and students’ mental health. Secondly, past researchers basically investigate only the direct effects between various stress related factors and other individual outcomes. However, less research has been done on identifying the mechanisms which may help to explain these relationships. Thus, this study focuses on outlying the propositions on the role of perceived stress as a potential mediator between stress related factors of academic pressure, family pressure, side activity pressure and financial pressure; and one aspect of individual outcomes (students’ mental health). Besides, emotional intelligence is proposed as the potential moderator than buffer the relationships. The relationships among the variables are discussed through the lens of Transactional Model of Stress and Coping. Lastly, suggestions for future studies are proposed.